Bismuth-Catalyzed Oxidative Coupling of Arylboronic Acids with Triflate and Nonaflate Salts - Planas, Oriol (J Am Chem Soc, 2020)
[Image: see text] Herein we present a Bi-catalyzed cross-coupling of arylboronic acids with perfluoroalkyl sulfonate salts based on a Bi(III)/Bi(V) redox cycle. An electron-deficient sulfone ligand proved to be key for the successful implementation of this protocol, which allows the unusual construction of C(sp(2))–O bonds using commercially available NaOTf and KONf as coupling partners. Preliminary mechanistic studies as well as theoretical investigations reveal the intermediacy of a highly electrophilic Bi(V) species, which rapidly eliminates phenyl triflate.